Population estimate of people with clinical Alzheimer's disease and mild cognitive impairment in the United States (2020-2060) - Rajan, Kumar B; Weuve, Jennifer; Barnes, Lisa L; McAninch, Elizabeth A; Wilson, Robert S; Evans, Denis A (Alzheimer's & dementia, 2021)
The estimate of people with clinical Alzheimer's disease (AD) and mild cognitive impairment provides an understanding of the disease burden. We estimated people with cognitive impairment using a quasibinomial regression model in 10,342 participants with cognitive test scores. The 2020 US Census-adjusted prevalence of clinical AD was 11.3% (95% confidence interval [CI] = 10.7-11.9): 10.0% among non-Hispanic Whites, 14.0% among Hispanics, and 18.6% among non-Hispanic Blacks. We estimate that in 2020, 6.07 (95% CI = 5.75-6.38) million people were living with clinical AD, which increases to 13.85 (95% CI = 12.98-14.74) million in 2060, 423% higher among Hispanics, 192% higher among Blacks, and 63% higher among Whites. However, there are predicted to be more significant increases in later years among those over 85 and women compared to men. The number of people with clinical AD will increase as the "baby boom" generation reaches older ages, exerting a strong upward influence on disease burden.